The Effectiveness of Agak Laen Official Daily Vlog in Enhancing Audience Enthusiasm For The Film "Agak Laen" - Amri, Khairul; Rozi, Fakhrur (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze the effectiveness of using daily vlogs in the marketing strategy of the film "Agak Laen" and understand how this approach influences audience enthusiasm. In the digital era that focuses on visual and interactive content, the success of a film depends not only on its production quality but also on the effectiveness of its marketing strategies. The urgency of this research lies in the need to understand the ever-changing dynamics of digital marketing and assess the potential of daily vlogs as an innovative marketing tool in the film industry. Utilizing a qualitative methodology with a field study approach, this research collects data through interviews, observations, and content analysis from the Official Agak Laen social media, as well as secondary sources such as reports and relevant literature. The study's findings reveal: First, the "Social Media Marketing Model of the Film Agak Laen" demonstrates that the integration of daily vlogs into the marketing strategy allows for deeper and more personal interactions with the audience, enhancing engagement and supporting the viral spread of content. Second, "Critique of Marketing Communication for Daily Vlog Film 'Agak Laen'" discusses the challenges faced, including the risk of over-saturation and audience skepticism towards aggressively promoted content. The study identifies that although daily vlogs are an effective tool for increasing visibility and engagement, this approach requires high authenticity and strategic management to avoid potential negative effects such as content fatigue among the audience. The recommendations include enhancing content personalization, utilizing audience analytics for better targeting, and balancing between promotion and providing added value to viewers.